2,5-Bis(2-naphthylmethylsulfanyl)-1-thia-3,4 diazacyclopenta-2,5-diene - How, Fiona Ni Foong; Watkin, David J.; Crouse, Karen Anne; Mohamed Tahir, Mohamed Ibrahim (International Union of Crystallography, 2007)
The title molecule, C24H18N2S3, consists of three essentially planar fragments viz. two methylnaphthalene groups and a five-membered thiadiazole ring. The dihedral angles between the two methylnaphthalene groups and the central 1-thia-3,4-diazacyclopenta-2,5-diene group are 78.9 (1) and 68.8 (1)°. In the crystal structure, - stacking interactions exist between pairs of symmetry-related naphthalene fragments with an interplanar separation of 3.35 Å. All bond lengths and angles are comparable with previous reports except that both C-S bond lengths are slightly longer than normal. In addition, the C-S-C and S-C-C bond angles appear to be smaller than normal and this could be due to the steric hindrance of the methylnaphthalene fragments.